2021
DOI: 10.1038/s41598-021-00323-5
|View full text |Cite
|
Sign up to set email alerts
|

Excess soluble alkalis to prepare highly efficient MgO with relative low surface oxygen content applied in DMC synthesis

Abstract: The activities of various MgO catalysts, which were prepared from different methods such as hydration synthesis, thermal decomposition, combustion, sol–gel and co-precipitation, were conducted in dimethyl carbonate (DMC) synthesis via transesterification of ethylene carbonate with methanol. MgO-P-Na2CO3-3.14 synthesized by the excess Na2CO3 precipitation compared the best catalytic activity and stability, which could be reused for seven times without obvious deactivation. The DMC yield was as high as 69.97% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The products were analyzed by a GC-2010 plus gas chromatography. The EC conversion, DMC selectivity, and DMC yield refer to the previous work …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The products were analyzed by a GC-2010 plus gas chromatography. The EC conversion, DMC selectivity, and DMC yield refer to the previous work …”
Section: Methodsmentioning
confidence: 99%
“…Based on the research in previous work, 22 the mechanism of EC transesterification with a MeOH catalyst by PS-IMC4IM was proposed, and the results are shown in Figure 8. The imidazole anion in PS-IMC4IM can activate methanol to methoxy anion, which has nucleophilicity and can attack the carbonyl carbon on EC to transform into ionic intermediates, and the intermediates react with H + in imidazole to form the hydroxyethyl methyl carbonate (HEMC).…”
Section: Mechanism Of Transesterification Reaction Catalyzed By Ps-im...mentioning
confidence: 99%
See 1 more Smart Citation
“…The O 1s spectra showed that the peaks related to -OH were derived from the chemisorbed -OH groups on the surface of MgO during steaming with binding energy values of 531.89 eV, 532.03 eV, and 531.89 eV for 10-min, 15-min, and 20-min steam exposed samples. It was seen that the peak intensities in the Mg 2p spectra increased with increased steaming time, indicating the improved formation of Mg(OH)2 due to the chemisorption of -OH in MgO [28].…”
Section: Structural and Morphological Characterizationmentioning
confidence: 97%
“…MgO exhibits excellent catalytic activity due to its high surface area and inherent basicity, which are crucial for facilitating the transesterification reaction [11]. The stability of MgO under the reaction conditions is noteworthy, as it maintains its structural integrity and catalytic performance, making it a strong choice both for continuous and batch processes [12][13][14]. Mg-doped CaO-MgO catalysts prepared by co-precipitation showed improved activity and stability in transesterification for biodiesel production.…”
Section: Introductionmentioning
confidence: 99%